Prognostic roles of leptin‐signaling proteins, PD‐L1, and tumor‐infiltrating lymphocytes in surgically‐resected biliary tract cancers. Issue 4 (11th November 2022) - Byeon, Sun‐ju; Chang, Mee Soo; Cho, Hwa Jin; Park, Jeong Hwan; Kim, Ki Hwan; Park, Jin Hyun; Choi, In Sil; Kim, Won; Han, Dong‐Seok; Ahn, Hye Seong; Heo, Seung Chul
Abstract: Background: Biliary tract cancers are rare, with a poor patient prognosis. Leptin and programmed death‐ligand 1 (PD‐L1) influence CD8 + and forkhead box P3 (FOXP3) + lymphocytes, and thus, cancer cell growth. We aimed to define the prognostic implications of these variables and the clinicopathological features of biliary tract cancers. Methods: Immunohistochemistry for leptin signaling‐related proteins (leptin, leptin receptor, pSTAT3, extracellular‐regulated kinase, mammalian target of rapamycin), PD‐L1, CD8, and FOXP3 and in situ hybridization for Epstein−Barr virus‐encoded small RNAs were performed in 147 cases of surgically‐resected biliary tract cancers. Results: Immune cell PD‐L1‐positivity, tumor size < 3 cm, adjuvant chemotherapy, no recurrence, and early‐stage tumors were correlated with better 5‐year survival in the tumoral PD‐L1 (–) and leptin (–) subgroups, and extrahepatic cholangiocarcinoma through multivariate analysis (all p  < 0.05). Immune cell PD‐L1 and adjuvant chemotherapy lost its prognostic significance in the tumoral PD‐L1 + and leptin + subgroups. Conclusions: The prognostic implication of the variables may depend upon tumoral protein expression and the anatomical site. Immune cell PD‐L1‐positivity and the administration of adjuvant chemotherapy may indicate the favorable survival of patients with surgically‐resected biliary tract cancers, specifically, in the tumoral PD‐L1 (–) or tumor leptin (–) subgroups and extrahepatic cholangiocarcinoma. PD‐L1‐ or leptin‐targeted therapy combined with conventional chemotherapy may benefit the tumoral PD‐L1 + or leptin + subgroups.